2011
DOI: 10.1245/s10434-011-2141-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Age, Stage Distribution, and Survival of Patients with Esophageal Adenocarcinoma over Three Decades in the United States

Abstract: There has been a substantial improvement in overall survival among patients with invasive EAC over the last 3 decades. Patients receiving esophagectomy had longer survival. Survival with esophagectomy improved in each time period. Although younger EAC patients were diagnosed at more advanced stages over time, they had better survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Increase in incidence of adenocarcinoma is primarily responsible for the rise in esophageal cancer in western world [2]. Majority of patients with esophageal adenocarcinoma present with loco-regional (stage II-III) disease.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in incidence of adenocarcinoma is primarily responsible for the rise in esophageal cancer in western world [2]. Majority of patients with esophageal adenocarcinoma present with loco-regional (stage II-III) disease.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 20 years, the incidence of squamous-cell carcinomas has decreased in the United States, while the rate of adenocarcinoma has increased [3]. Smoking and obesity may account for some of these changes[1].…”
Section: Introductionmentioning
confidence: 99%
“…4 Some randomized trials suggest that preoperative chemotherapy has a survival benefit in resectable AC of the stomach, EGJ, or lower esophagus; however, esophageal AC only accounted for 10%-15% of the cases. 10,59 A metaanalysis on preoperative chemotherapy trials in esophageal cancers, including nine randomized comparisons of neoadjuvant chemotherapy vs surgery alone (n=1,981), provided the strongest evidence for a survival benefit of neoadjuvant chemotherapy over surgery alone in patients with esophageal carcinoma with an hazard ratio (HR) of 0.87 (95% confidence interval [CI], 0.79-0.96; P=0.005). 40 Similarly, a Cochrane review including 14 randomized trials of AC of the stomach, EGJ, and lower esophagus also demonstrated that preoperative chemotherapy was associated with a significantly longer OS.…”
Section: Neoadjuvant Chemotherapy and Surgery Vs Surgery Alonementioning
confidence: 99%
“…Over the past 3 decades, surgical advances and improvement in radiation techniques have greatly improved the disease outcomes. [9][10][11] This article focuses on integrating these approaches and tailoring the treatment strategy for individual patients, compares the effectiveness of the various treatment approaches in the definitive or neoadjuvant…”
Section: Introductionmentioning
confidence: 99%